De experiencias y elecciones: narrativas de adolescentes adoptadas en el área metropolitana de Buenos Aires, Argentina - Carolina Ciordia (Confluenze, 2022)
From an anthropological perspective, it is analyzed how adolescents have meant their own adoptions, focusing on two aspects of the adoption process: how they became aware of the existence of adoption as a possible outcome for their personal trajectory, thus building an experiential knowledge; and the experiences associated with the suffering that they went through in the institutional care facilities where they were housed and in the outcomes of their adoptions. The pain and suffering that the adolescents adopted in these processes went through can be interpreted as stages in the preparation of the subjects for a change in status.